Cournot vs. Bertrand under centralised bargaining - Basak, Debasmita (Elsevier, 2017)
We revisit the debate on Cournot and Bertrand profit comparison in a vertically related upstream market for inputs. We find that when an input pricing contract is determined through centralised bargaining, the final goods producers earn higher (lower) profit under quantity competition than under price competition if the goods are substitutes (complements). Our results are strikingly different to the ones obtained from a similar comparison in other vertical pricing models.